The Effectiveness of Gender Based Class Segregation in Preventing Dating Behavior in Junior High Schools - Salsabila Tajrin; Budi Haryanto (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2026)
Dating behavior among junior high school students has the potential to impact student focus and character development. As a preventative measure, Islamic educational institutions implement a gender segregation policy by separating classes between boys and girls. This study aims to describe student dating behavior and explore the effectiveness of gender segregation in preventing such behavior at